2022
DOI: 10.1088/1361-6498/ac6044
|View full text |Cite
|
Sign up to set email alerts
|

Changes of the linear energy transfer (LET) and beam width of therapeutic carbon ion beam in density heterogeneous phantoms

Abstract: This work aims to investigate the changes in the linear energy transfer (LET) spectra distribution and the beam spot width of a therapeutic carbon ion beam in density heterogeneous phantoms. Three different heterogeneous phantoms were fabricated using a combination of solid water, lung, and bone tissue slabs and irradiated by a single energy carbon beam (276.5 MeV/u). CR-39 detectors were used for experimental measurements and the Monte Carlo toolkit Geant4 was employed for theoretical simulations. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Among all these detectors, CR-39 and TLD are relatively convenient to be placed inside phantoms. Our previous studies (Yang et al 2022a(Yang et al , 2022b and that of other researchers (Bilski 2010) had demonstrated the capabilities of these two detectors in LET measurements. Each of these two detectors had its own limitations, such as lack of response to particles with low LET for CR-39 (Kodaira et al 2016, Hirano et al 2018 as well as the unclear measurement mechanism for the TLD (Horowitz et al 2003).…”
Section: Introductionmentioning
confidence: 87%
“…Among all these detectors, CR-39 and TLD are relatively convenient to be placed inside phantoms. Our previous studies (Yang et al 2022a(Yang et al , 2022b and that of other researchers (Bilski 2010) had demonstrated the capabilities of these two detectors in LET measurements. Each of these two detectors had its own limitations, such as lack of response to particles with low LET for CR-39 (Kodaira et al 2016, Hirano et al 2018 as well as the unclear measurement mechanism for the TLD (Horowitz et al 2003).…”
Section: Introductionmentioning
confidence: 87%
“…Ziegler et al [6] have studied the energy loss and radiation damage in anthracene using the SRIM Monte Carlo code for 100 keV heavy ion irradiation. Yang et al investigated the LET and beam spot width of the carbon ion beam in different heterogeneous phantoms [12]. MSP and PR are calculated for H 1 (proton particles) and He +2 (alpha particles) of La 2 O 3 glasses with different software by Kilicoglu et al [13].…”
Section: Introductionmentioning
confidence: 99%
“…Limiting entropy ratios for carbon ions were computed by Geithner et al [17]. In another study, stopping power compilations were studied for alpha particle, proton, 12 C, 16 O, and 56 Fe for the target aluminum, copper, iron, and silicon [18]. In Correa's study, he explained in detail how the electronic stopping power in the materials was calculated [4].…”
Section: Introductionmentioning
confidence: 99%